Src Is a Potential Therapeutic Target in Endocrine-Resistant Breast Cancer Exhibiting Low Estrogen Receptor-Mediated Transactivation - Guest, Stephanie K. (PLoS One, 2016)
Despite the effectiveness of endocrine therapies in estrogen receptor positive (ER+) breast cancer, approximately 40% of patients relapse. Previously, we identified the Focal-adhesion kinase canonical pathway as a major contributor of resistance to estrogen deprivation and cellular-sarcoma kinase (c-src) as a dominant gene in this pathway. Dasatinib, a pan-src inhibitor, has recently been used in clinical trials to treat ER+ patients but has shown mixed success. In the following study, using isogenic cell line models, we provide a potential explanation for these findings and suggest a sub-group that may benefit. A panel of isogenic cell lines modelling resistance to aromatase inhibitors (LTED) and tamoxifen (TAMR) were assessed for response to dasatinib ± endocrine therapy. Dasatinib caused a dose-dependent decrease in proliferation in MCF7-TAMR cells and resensitized them to tamoxifen and fulvestrant but not in HCC1428-TAMR. In contrast, in estrogen-deprived conditions, dasatinib increased the proliferation rate of parental-MCF7 cells and had no effect on MCF7-LTED or HCC1428-LTED. Treatment with dasatinib caused a decrease in src-phosphorylation and inhibition of downstream pathways, including AKT and ERK1/2 in all cell lines tested, but only the MCF7-TAMR showed a concomitant decrease in markers of cell cycle progression. Inhibition of src also caused a significant decrease in cell migration in both MCF7-LTED and MCF7-TAMR cells. Finally, we showed that, in MCF7-TAMR cells, in contrast to tamoxifen sensitive cell lines, ER is expressed throughout the cell rather than being restricted to the nucleus and that treatment with dasatinib resulted in nuclear shuttling of ER, which was associated with an increase in ER-mediated transcription. These data suggest that src has differential effects in endocrine-resistant cell lines, particularly in tamoxifen resistant models, with low ER genomic activity, providing further evidence of the importance of patient selection for clinical trials testing dasatinib utility in ER+ breast cancer.